Pemahaman Konsep Pereaksi Pembatas Hasil Pembelajaran Kimia Menggunakan LKS-Induktif Pada Siswa Kelas X - Ike Valentie (FKIP Universitas Palangka Raya, 2019)
Concept of limiting reagents is part of stoichiometry. This means that to learn the limiting reagent material students must have understood and mastered the prerequisite concepts namely chemical formulas, chemical equations and mole concepts. This study aims to: describe the understanding of the concept of SMA Negeri 1 Palangka Raya students about limiting reagents before and after learning using worksheet-inductive. This study involved 68 students of class X Science-1 and X Science-4 of Public Senior High School 1 Palangka Raya. The instrument used was a pretest and posttest question sheet, Worksheet-Inductive. Data was collected through three stages, namely pretest, implementation of learning by using Worksheet-Inductive, and posttest. The data obtained were analyzed descriptively. The results showed that the understanding of the concept of limiting students 'reagents at pretest was 3.36% and understanding of students' concepts at posttest was 69.32%. Changes in students' understanding of concepts increased by 65.96% can be classified into either category. In detail the understanding of the concept of limiting students' reactants as follows: a) understanding of the concepts defining the definition of limiting reactants by 52.58%; (b) understanding of the concept of determining limiting reagents is 69.32%.